2018
DOI: 10.1097/rli.0000000000000426
|View full text |Cite
|
Sign up to set email alerts
|

Intravoxel Incoherent Motion Analysis of Abdominal Organs

Abstract: Simultaneous multislice acceleration provides considerable scan time reduction for upper abdomen DWI with equivalent quality of IVIM analysis compared with the standard nonaccelerated technique. Systematic discrepancies of the true Dt, D*, and Fp for SMS acquisitions need to be considered when comparing to standard DWI sequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 24 publications
0
6
1
Order By: Relevance
“…Phi Van et al 27 evaluated the accuracy of IVIM analysis of the parenchymal abdominal organs using SMS-DWI and found that the D values increased and f values decreased significantly with higher AFs. In the present study, higher AFs, lower D and D* values in the liver, and lower D* values in the pancreas were observed; however, these values did not follow similar patterns in other organs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phi Van et al 27 evaluated the accuracy of IVIM analysis of the parenchymal abdominal organs using SMS-DWI and found that the D values increased and f values decreased significantly with higher AFs. In the present study, higher AFs, lower D and D* values in the liver, and lower D* values in the pancreas were observed; however, these values did not follow similar patterns in other organs.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Several studies have reported that the SMS technique can shorten the DWI scan time in different organs. [18][19][20][21][22][23][24][25][26] However, a limited number of studies 22,27 have focused on IVIM analysis based on SMS-DWI sequences and found a significant scan time reduction. Phi Van et al 27 reported slight systematic deviations in the IVIM parameters with increased AFs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…43 The multislice signal can be deconvoluted based on coil sensitivity profiles of multichannel array coils, controlled aliasing in parallel imaging results in higher acceleration (CAIPIRINHA), and field of view shifting. 44 Simultaneous multislice acquisition techniques can be applied to various pulse sequences, including 2D diffusion-weighted imaging [45][46][47] and 2D TSE pulse sequences. 48 Modern blipped simultaneous multislice acquisition techniques are nearly signal neutral because of the sole signal-to-noise reduction dependency on g-factor loss.…”
Section: Acceleration Techniquesmentioning
confidence: 99%
“…16 The occurring SNR decrease (40% for acceleration factor of 2) is balanced by improved surface coil design and SNR at 3 T. For small structures reduced field of view (zoomed), imaging enables an increased resolution while reducing geometric distortions. 27 Simultaneous multislice DWI can be used to reduce scan time at 3 T. 28 For good fat suppression at 3 T, STIR (short TI inversion recovery) is useful, especially in diffusion-weighted whole-body imaging with background body signal suppression (DWIBS). 21,29 STIR provides low sensitivity against magnetic field inhomogeneity by suppressing body parts with short T1 relaxation times (eg, fat, intestine, or areas of gadolinium enhancement).…”
Section: Solutionsmentioning
confidence: 99%